2011
DOI: 10.1002/pssb.201147156
|View full text |Cite
|
Sign up to set email alerts
|

Dual action of light in photodarkened Ge–As–S films

Abstract: In annealed chalcogenide films, thinner than 1 mm, highly expressed photodarkening (PD) can be fully restored after prolonged illumination. It was supposed that this light annealing effect (LAE) results from the dual action of light, which provokes not only increase of network disorder at PD but also decrease of disorder leading to photobleaching (PB), competing with PD. To confirm it, the changes of two parameters of disorder are studied: the Tauc slope B 1/2 , dependent on network bonding character, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The dual action of light was shown earlier in Ge-As-S [22,23] and in Ge-As-Se [24] films. In essence, this shows the reversibility of the processes for which Elliott has created a unified model [25].…”
Section: Discussionsupporting
confidence: 54%
“…The dual action of light was shown earlier in Ge-As-S [22,23] and in Ge-As-Se [24] films. In essence, this shows the reversibility of the processes for which Elliott has created a unified model [25].…”
Section: Discussionsupporting
confidence: 54%
“…that As 2 S 3 and GeS 2 expand under illumination. It is also known that GeAs-S(Se) ternary glasses possess a unique characteristic, photoinduced volume compaction (Hamanaka et al, 1976;Calvez et al, 2009;Arsova and Vateva, 2012). Nevertheless, all these glasses exhibit photodarkening.…”
Section: Remaining Problemsmentioning
confidence: 98%
“…Recent studies demonstrate that the transition between these two effects becomes apparent with an increase of the exposure time. This demonstrates the dual role of light for occurrence of PIEs in ChG [25][26][27]. It also has been found that light-induced effects are composition dependent and can transition from photodarkening to photobleaching with change from Ge-deficient to Ge-rich material [28].…”
Section: Introductionmentioning
confidence: 60%